Webpage ranking : how it affects your selections - Zhang, Boyu (2011)
What do you need to search for your desired answer? Recalling the period before 1997, the most possible would be “go the libraries”. And now, the most possible answer is a computer with internet connected to find it out on the search engines. Web site like Google, Bing and Yahoo etc. are all commonly used search engine. These search engines will provide long lists of website for each query. How would the user decide the result they really desire? According to the research results from Chitika, a worldwide search-targeted network, the highest Google result impressions percentage is the result listed in the first position at 34.5%. As shown in the result, webpage ranking greatly affect the choices made by the users.